USING DICTOGLOSS AS AN EFFECTIVE METHOD TO IMPROVE STUDENTS SKILL IN LISTENING NARRATIVE STORY - Suryadi, Ray; Serly, Serly; Abin, Rais; Hodairiyah, Hodairiyah (JOEEL (Journal of English Education and Literature), 2023)
This research was conducted at SMP Negeri 1 Tinondo. The research purpose is to find out whether there is a significant effect of Dictogloss method on Listening skill of Narrative text at the second grade students of SMPN 1 Tinondo. The population of this research consists of 43 students. From the population, there were 22 students were taken as a sample of experimental class and 21 students were control class. The sample was taken using saturation sampling. The research method used in this research is a quantitative method using quasi experimental method. The data collected through pre-test and post-test. This aims to determine whether there is an effect of Dictogloss Method on the students' listening skill of narrative texts. The data analyzed by using t-test which showed that the value of t-test (to) was higher than t-table (tt), to > tt = 32.023 > 1,717 in a significant degree of 0,05 %. It means that the alternative hypothesis (ha) was accepted and the Null hypothesis (ho) was rejected. In conclusion, The Dictogloss method has an effect on students' listening skill.